Estimating a social cost of carbon for global energy consumption - Rode, Ashwin; Carleton, Tamma; Delgado, Michael; Greenstone, Michael; Houser, Trevor; Hsiang, Solomon; Hultgren, Andrew; Jina, Amir; Kopp, Robert E.; McCusker, Kelly E.; Nath, Ishan; Rising, James; et al. (Nature (London), 2021)
Estimates of global economic damage caused by carbon dioxide (CO 2 ) emissions can inform climate policy 1 – 3 . The social cost of carbon (SCC) quantifies these damages by characterizing how additional CO 2 emissions today impact future economic outcomes through altering the climate 4 – 6 . Previous estimates have suggested that large, warming-driven increases in energy expenditures could dominate the SCC 7 , 8 , but they rely on models 9 – 11 that are spatially coarse and not tightly linked to data 2 , 3 , 6 , 7 , 12 , 13 . Here we show that the release of one ton of CO 2 today is projected to reduce total future energy expenditures, with most estimates valued between −US$3 and −US$1, depending on discount rates. Our results are based on an architecture that integrates global data, econometrics and climate science to estimate local damages worldwide. Notably, we project that emerging economies in the tropics will dramatically increase electricity consumption owing to warming, which requires critical infrastructure planning. However, heating reductions in colder countries offset this increase globally. We estimate that 2099 annual global electricity consumption increases by about 4.5 exajoules (7 per cent of current global consumption) per one-degree-Celsius increase in global mean surface temperature (GMST), whereas direct consumption of other fuels declines by about 11.3 exajoules (7 per cent of current global consumption) per one-degree-Celsius increase in GMST. Our finding of net savings contradicts previous research 7 , 8 , because global data indicate that many populations will remain too poor for most of the twenty-first century to substantially increase energy consumption in response to warming. Importantly, damage estimates would differ if poorer populations were given greater weight 14 . Using global data, econometrics and climate science to estimate the damages induced by the emission of one ton of carbon dioxide, climate change is projected to increase electricity spending but reduce overall end-use energy expenditure.